Improving Service Quality To Enhance The Sustainability Of Higher Education : (Case Study: Division of Creativity and Study Consultation, University X) - Kuriawan, Axel Varian; Talar, Yulianti (RSF Conference Series: Business, Management and Social Sciences, 2022)
HE institutions need to continuously improve their quality to be able to compete and maintain their sustainability. The Division of Creativity and Study Consultation (CSC) is a division at University X, which plays a major role in promoting University X. Various complaints from prospective new students and their parents have been received regarding the inaccurate delivery of the information provided. This study aims to determine the satisfaction index of prospective students/parents with the Division of CSC and propose improvements for the Division of CSC based on the expectation of prospective students/parents and the performance of the Division of CSC. Data was collected using a questionnaire based on the SERVQUAL Model. Questionnaires gathered from 100 respondents who meet the purposive sampling requirements, namely prospective students or their parents who have received services (online or offline services) from the Division of CSC from promotion until admissions, have seen the University X website/social media, and have received services from the Division of CSC via telephone or email. Consumers’ expectations and performance of the Division of CSC were processed using the Gap Analysis Model, hypothesis testing for 2-paired-means, Consumer Satisfaction Index, and Importance-Performance-Analysis (IPA). A cause-effect diagram consisting of 8 Ps (People, Process, Policies, Procedures, Price, Promotion, Place, Product) is used to find out the root of the problem. The suggestions from this research are training for the Division of CSC staff, making direct and indirect delivery procedures, and developing market research to support service activities.